Meningkatkan Pendapatan Asli Daerah melalui Pajak Restoran dengan Penerapan Tapping Box - Ramadhani, A. Murya; Agusman, Yudi; Ashari, Ashari; Hidayat, Rahmat (CV. Social Politic Genius (SIGn), 2022)
This research aims to explore the contribution of tapping boxes in enhancing Regional Revenue through restaurant taxes. This research uses an inductive qualitative analysis. Inductive analysis is an approach that begins with field facts, analyzes them based on relevant theories and arguments, and ultimately yields a conclusion. The results show that implementing tapping boxes in Kolaka Regency has effectively increased Regional Revenue through restaurant taxes. However, there are shortcomings in the distribution of the devices, resulting in not all qualified restaurants being equipped with tapping boxes. A significant challenge arises from customers adjusting to price changes due to tax transparency, leading to a decrease in customer numbers by up to 30% in some restaurants. Ultimately, although the contribution of restaurant taxes to Regional Revenue has increased significantly, customer satisfaction and the effectiveness of tapping box distribution require further attention to balance fiscal success with the sustainability of restaurant businesses. Therefore, it is recommended that the Local Government and the Regional Revenue Agency of Kolaka Regency improve the effectiveness of tapping box distribution by ensuring that all restaurants meeting the criteria are equipped with the devices while also conducting evaluations and adjusting the installation criteria to avoid discrepancies. Restaurant owners are advised to adopt innovative business strategies to counteract the decline in customer numbers, such as by enhancing service quality or implementing customer loyalty programs. Meanwhile, as customers, the public must be educated about the importance of tax transparency and its contribution to regional development to understand better and accept price changes. Through a collaborative approach among the government, restaurant owners, and the public, a balance between increasing Regional Revenue and the sustainability of restaurant businesses and long-term customer satisfaction is expected to be achieved.